Insight from expression profiles of FT orthologs in plants: conserved photoperiodic transcriptional regulatory mechanisms - Lee, Nayoung; Shim, Jae Sung; Kang, Min-Kyoung; Kwon, Moonhyuk (Frontiers in Plant Science, 2024)
Floral transition from the vegetative to the reproductive stages is precisely regulated by both environmental and endogenous signals. Among these signals, photoperiod is one of the most important environmental factors for onset of flowering. A florigen, FLOWERING LOCUS T (FT) in Arabidopsis, has thought to be a major hub in the photoperiod-dependent flowering time regulation.Expression levels of FT likely correlates with potence of flowering. Under long days (LD), FT is mainly synthesized in leaves, and FT protein moves to shoot apical meristem (SAM) where it functions and in turns induces flowering. Recently, it has been reported that Arabidopsis grown under natural LD condition flowers earlier than that grown under laboratory LD condition, in which a red (R)/ far-red (FR) ratio of light sources determines FT expression levels. Additionally, FT expression profile changes in response to combinatorial effects of FR light and photoperiod. FT orthologs exist in most of plants and functions are thought to be conserved. Although molecular mechanisms underlying photoperiodic transcriptional regulation of FT orthologs have been studied in several plants, such as rice, however, dynamics in expression profiles of FT orthologs have been less spotlighted. This review aims to revisit previously reported but overlooked expression information of FT orthologs from various plant species and classify these genes depending on the expression profiles. Plants, in general, could be classified into three groups depending on their photoperiodic flowering responses. Thus, we discuss relationship between photoperiodic responsiveness and expression of FT orthologs. Additionally, we also highlight the expression profiles of FT orthologs depending on their activities in flowering. Comparative analyses of diverse plant species will help to gain insight into molecular mechanisms for flowering in nature, and this can be utilized in the future for crop engineering to improve yield by controlling flowering time.